Technology Acceptance Model (TAM) Dalam Evaluasi Pelaksanaan Rekam Medis Elektronik di Rumah Sakit - wulandari, fitria; Maureta, Rizkyana Putri; Agung, wardoyo (Jurnal Kesehatan, 2025)
Hospital X in Semarang City has transitioned from paper-based medical records to electronic medical records (EMRs) in its outpatient unit. However, the implementation has faced obstacles, particularly frequent system response failures (freezing), especially in the billing system, which has disrupted service delivery. This study aimed to analyze and assess the readiness of outpatient unit staff at Hospital X in implementing EMRs. The study used a quantitative descriptive approach, collecting data through questionnaires that assessed perceived usefulness, perceived ease of use, staff readiness, and attitudes toward EMRs. The population included 23 outpatient unit staff members actively using the EMR system, comprising 4 registration officers, 10 polyclinic nurses, and 9 pharmacists. Total sampling was employed, and responses were measured using a Likert scale to determine the level of agreement with various statements. The results showed that 19 officers were categorized as "ready," 3 as "very ready," and 1 as "neutral." Most of those in the "ready" and "very ready" categories were female, held diplomas, and had 1–5 years of work experience. The officer in the "neutral" category was a female aged 44–52, also with a diploma, but with over 10 years of work experience. Based on the four dimensions of the Technology Acceptance Model (TAM), the highest score was in the Perceived Usefulness dimension (81.96%), followed by Behavioral Intention to Use (81.74%), Attitude Toward Using (75.87%), and Perceived Ease of Use (72.55%). It is recommended that staff with only a high school education receive additional training. The officer in the "neutral" category should be re-evaluated to identify challenges in using EMRs, and experienced staff with over 10 years of service may be motivated through rewards to encourage greater enthusiasm in adapting to the EMR system. Keywords: Electronic Medical Records, TAM, Hospital.